Competition of Triticale (Triticosecale wittmack) Lines with Wild Oat (Avena fatua) and its Different Densities - M. Najjari Sadeghi,; B. Mirshekari; A.H. HosseinZadeh Moghbeli; S. Baser Kouchebagh (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī, 2014)
To study competitive effects of different densities of wild oat (Avena fatua) with triticale lines an experiment was conducted at Research Station of Islamic Azad University, Tabriz Branch, Tabriz, Iran during 2011-2012 with 3 replications. Treatments were 19 triticale lines and 6 densities of wild oat (0, 40, 80, 120, 160 and 200 plants m-2). Results indicated that effects of wild oat densities on thousand seed weight and seed yield of triticale lines were significant at 1% probability level. Also, tiller number per plant and biological yield of triticale lines were affected by the weed densities. While, wild oat traits under study were not affected by triticale lines. Hexaploid lines of triticale could tolerate 40 weed plants m-2 without any significant reduction in1000 seed weight. Wild oat density of 120 and higher plants m-2 had negative effect on seed yield of hexaploid lines of triticale.